(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2025)
The Golfo San Jorge Basin (GSJB) preserves the thickest Cenozoic stratigraphic record in extra-Andean Patagonia (Argentina), reaching approximately 1500 meters. This record was subdivided into three major second-order transgressive regressive (TST-RST) sedimentary sequences: (1) The early Paleogene T-R cycle ( 600 m thick; early Paleocene–late Eocene), comprising the Salamanca Formation (marine), Río Chico Group (fluvial), and part of Sarmiento Formation (pyroclastic loess). This sequence reflects a marine-to-continental transition, with an early marine stage marked by tidally-influenced, shallow-marine and inner-shelf sedimentation, followed by fluvial systems and long-lived accumulation and reworking of fine ash in a low-gradient continental setting. (2) The late Paleogene-early Neogene T-R cycle ( 200 m thick, late Eocene-early Miocene), composed of the El Huemul Formation (marine) and the upper part of Sarmiento Formation (pyroclastic deposits). (3) The Neogene T-R cycle ( 700 m thick; early–middle Miocene), includes the Chenque Formation (marine) and the Santa Cruz or Escalante Formation (fluvial-eolian). The three marine second order TSTs share similar temporal duration (<5 million years) and sedimentation patterns are strongly influenced by continental slope inheritance. However, the continental second-order RSTs differ significantly: (i) the early Paleogene RST lasted 22 million years, compared with the 10 million years of the late Paleogene-early Neogene cycle and the 5 million years of the Neogene; (ii) the Paleogene records extensive global climatic fluctuations, whereas the Neogene is characterized by a single wet to dry cycle; (iii) pyroclastic deposits dominate the early Paleogene and late Paleogene-early Neogene sequences, but they are nearly absent in the Neogene; (iv) the first two second order continental cycles preserves an exceptional assemblage of continental mammal faunas, serving as a biostratigraphic reference for South America. Although the GSJB’s macrostratigraphy correlates strongly with regional sea-level fluctuations, additional controlling factors have been proposed, including extensional tectonic reactivations, Andean orogenic uplift, intrusion-related tectonic loading, sustained pyroclastic input, climatic variability, and dynamic topography.